Students’ Responses Toward The Use of SQ3R Method in Teaching Reading Comprehension - Arifah, Rifa Rifkiati; Santoso, Iman (IKIP Siliwangi, 2025)
This research investigates students’ responses in using the SQ3R method in teaching reading comprehension. The respondents of this research were tenth-grade students at one Senior High School in Garut, with 27 students. The instruments used in this research were questionnaires and interviews. The data were analyzed through reduction, presentation, and conclusion. The results found that students' responses in teaching reading comprehension using the SQ3R method showed that the students gave positive responses. In conclusion, SQ3R can be an alternative method to teach reading. They could eliminate the wrong comprehension, get motivated, be interested, and dare to deliver opinions, especially in teaching reading comprehension.